Two-year results of switching to intravitreal administration of faricimab in patients with aflibercept-refractory neovascular age-related macular degeneration - Masaaki Saito; Kimihiro Imaizumi (Scientific Reports)
Abstract We evaluated the efficacy of switching to intravitreal injection of faricimab (IVF) in patients with aflibercept-refractory neovascular age-related macular degeneration (nAMD) over 2 years of follow-up. We retrospectively reviewed 47 consecutive eyes of 45 Japanese patients with nAMD who switched from aflibercept to faricimab. Thirty-one eyes of 30 Japanese patients were included in this study. The mean visual acuity (BCVA) at month 24 was stable relative to the baseline. The mean central retinal thickness and subfoveal choroidal thinning significantly decreased at 24 months (P < 0.0001, P < 0.0001, respectively). At 24 months, 22 eyes (70.0%) achieved a dry macula and had improved VA levels with an improvement of 0.80 lines, which was significantly different from the remaining 9 eyes (P < 0.01). The mean interval of IVF was 11.8 weeks, which was significantly longer than that of aflibercept (10.0 weeks) at baseline (p = 0.014). Progression of macular atrophy or newly developing macular atrophy was seen in 3 eyes (9.7%), showing decline of 1.0 line, no other complications were seen. These results indicate that switching to IVF stabilized VA, significantly improved the anatomical changes and the achievement of a dry macula was significantly associated with the visual outcome, in patients with aflibercept-refractory nAMD over a 24-month period.